German demonstrative pronouns differ in their sensitivity to discourse and sentence topics - Buchholz, Timo; von Heusinger, Klaus (Frontiers in Communication, 2024)
German has two demonstrative pronoun series, the short form der, die, das, and the long form dieser, diese, dieses. Both forms can be used anaphorically and they contrast with the personal pronoun er, sie, es in that they refer to an antecedent that is less prominent at that point in the discourse when the discourse provides different potential antecedents. Demonstrative pronouns are typically used in the preverbal position in a German sentence, i.e. the topic position. Thus, they are assumed to be topic shifters (from a non-topical antecedent to the topical argument in the current sentence). However, der can be repeated yielding topic chains, thus referring back to a topical antecedent, while this is not the case for dieser. In this paper, we argue that der and dieser both contribute to topic management, but they do this in different ways: der is a marker of a sentence topic, while dieser is a marker of discourse topic shift. We present the results of two experiments that compare the use of personal pronouns with either demonstrative pronoun manipulating sentence topic and discourse topic. First, both experiments show that the personal pronoun is not sensitive to either type of topichood of its antecedent. Second, Experiment 1 shows that both demonstrative pronouns prefer a context where discourse topic and sentence topic are shifted. Third, experiment 2 shows that only dieser prefers a context with a shifted discourse topic, but der is not sensitive to discourse topichood only. We take the results as supporting our claim that the two demonstratives have different discourse functions: der marks a sentence topic, while dieser is a shifter (and marker) of the discourse topic.